Coupled hygro-mechanical multiscale analysis of masonry walls. (1st February 2015) - Castellazzi, G.; de Miranda, S.; Formica, G.; Molari, L.; Ubertini, F.
Highlights: A coupled hygro-mechanical model for the analysis of masonry structures is presented. Fully coupling between mechanical response and moisture diffusion is considered. A robust multiscale framework allows to perform analysis at the engineering scale. Numerical applications are used to validate the model and show its effectiveness. Abstract: In this paper, a two-dimensional discrete coupled hygro-mechanical model for the multiscale analysis of masonry structures is presented. The model takes into account the effect of the diffusion of moisture within the masonry on the mechanical response as well as for the effect of the mechanical degradation on the diffusion process. The scope of the paper is to propose a robust numerical framework to perform a coupled hygro-mechanical analysis at the engineering scale. Numerical applications are presented to validate the model and show its effectiveness.